Hyperinsulinemia and plasma glucose level independently associated with all-cause and cardiovascular mortality in Chinese people without diabetes—A post-hoc analysis of the 30-year follow-up of Da Qing diabetes and IGT study. (January 2023) - Wang, Haixu; He, Siyao; Wang, Jinping; An, Yali; Wang, Xuan; Li, Guangwei; Gong, Qiuhong; ,
Abstract: Aims: We aimed to characterize the effect of insulin resistance and plasma glucose on all-cause and cardiovascular disease (CVD) death. Methods: A total of 462 individuals without diabetes in the original Da Qing Diabetes and IGT Study were enrolled in the present analysis, and further divided into G1 (low insulin low glucose), G2 (high insulin low glucose), G3 (low insulin high glucose) and G4 (high insulin high glucose) groups according to medians of glucose and insulin level at baseline. The all-cause and CVD death were assessed from 1986 to 2016. Results: During the 30-year follow-up, compared with G1, G2, G3, and G4 groups were all at increased death risk after adjusting covariates. G2 and G3 were associated with similar risks in both all-cause (G2: HR 1.65, 95%CI 1.02–2.67; G3: HR 1.76, 95%CI 1.11–2.81) and CVD death (G2: HR 2.03, 95%CI 1.01–4.05; G3: HR 1.85, 95%CI 0.93–3.68). The highest risk was observed in G4 (all-cause death: HR 2.32, 95%CI 1.45–3.69; CVD death: HR 2.68, 95%CI 1.35–5.29). Conclusions: In this post-hoc study, participants with either high glucose or high insulin were related to increased risk of mortality, implying that strategies targeting eliminating both hyperglycemia and hyperinsulinemia may favor the long-term outcomes.